Struktur Naratif Kisah Raja Dzulkarnain dalam Al-Qur’an: Analisis Semiotika Aktan A.J. Greimas - Alandira, Palendika; Taufiq, Wildan; Rohanda, Rohanda (Institut Agama Islam Ngawi, 2024)
This research aims to analyze the story of King Dhul-Qarnayn in the Qur'an using A.J. Greimas's actantial semiotics approach. The method used is a qualitative analysis of verses related to the character, role, and actions of King Dhul-Qarnayn, as well as his impact on the surrounding society. Through this analysis, it was found that King Dhul-Qarnayn functions as a mediator between God and humanity, establishing justice by upholding goodness and punishing wrongdoing. The study results show that King Dhul-Qarnayn's character embodies moral and social values relevant to societal life, providing lessons on responsibility and leadership in achieving collective well-being. This research is expected to provide a deeper understanding of the moral messages within the story of King Dhul-Qarnayn and their application in everyday life.